Combination of Broccoli Sprout Extract and Zinc Provides Better Protection against Intermittent Hypoxia-Induced Cardiomyopathy Than Monotherapy in Mice - Wang, Jiqun (Oxid Med Cell Longev, 2019)
Nuclear factor-E2-related factor 2 (Nrf2) and metallothionein have each been reported to protect against chronic intermittent hypoxia- (IH-) induced cardiomyopathy. Sulforaphane-rich broccoli sprout extract (BSE) and zinc can effectively induce Nrf2 and metallothionein, respectively, to protect against IH-induced cardiomyopathy via antioxidative stress. However, whether the cardiac protective effects of the combination of BSE and zinc can be synergistic or the same has not been evaluated. In this study, we treated 8-week-old C57BL/6J mice with BSE and/or zinc during exposure to IH for 8 weeks. Cardiac dysfunction, as determined by echocardiography, and pathological remodeling and abnormalities, including cardiac fibrosis, inflammation, and oxidative damage, examined by histopathology and western blotting, were clearly observed in IH mice but were not significant in IH mice treated with either BSE, zinc, or zinc/BSE. Furthermore, the effects of the combined treatment with BSE and zinc were always greater than those of single treatments. Nrf2 function and metallothionein expression in the heart increased to a greater extent using the combination of BSE and zinc than using BSE or zinc alone. These findings for the first time indicate that the dual activation of Nrf2 and metallothionein by combined treatment with BSE and zinc may be more effective than monotherapy at preventing the development of IH-induced cardiomyopathy.